2018
DOI: 10.1097/inf.0000000000001840
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Routine HIV Birth Testing in the South African National Consolidated Guidelines

Abstract: Universal birth testing for all HIV-exposed neonates is rapidly being achieved in South Africa, facilitating earlier detection of intrauterine infected neonates. However, the successful linkage into care of HIV-infected neonates and their treatment outcomes remain to be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…Data presented in a review of the first year of the SA National EID Programme demonstrated an increase in birth EID coverage from 39% (high‐risk) to 93% within 12 months of the national guideline change to universal birth testing with a corresponding drop in six‐week testing (to 19%); the increase in ten‐week tests was modest . In our study, the majority of all birth testing occurred in infants born in hospital.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Data presented in a review of the first year of the SA National EID Programme demonstrated an increase in birth EID coverage from 39% (high‐risk) to 93% within 12 months of the national guideline change to universal birth testing with a corresponding drop in six‐week testing (to 19%); the increase in ten‐week tests was modest . In our study, the majority of all birth testing occurred in infants born in hospital.…”
Section: Discussionmentioning
confidence: 43%
“…When the sample of exposed infants tested at birth is expanded to include those at low risk of infection, a reduced transmission rate would be expected. The average in utero transmission rate during the first year of the SA national birth EID programme was 1.1%; when stratified by province it was 2.6% in the Western Cape but the interval overlapped both period 2 and period 3 suggesting that the sample may have been biased towards high‐risk infants and is closer to that in period 2 . The discrepancy may also be due to the maternal HIV prevalence in our study sample (14.7% at delivery) versus 18.9% for the whole province .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…intensified case-finding initiatives, earlier diagnosis of HIV, and accelerated entry into care. [4] While there is evidence of improvements in HIV diagnosis and access to ART among children, [5,6] retention of children in HIV care remains a challenge.…”
Section: Researchmentioning
confidence: 99%
“…Early infant diagnosis (EID) of HIV, an essential component of the PMTCT programme, includes routine HIV polymerase chain reaction (PCR) testing at birth and 10 weeks of age for all HIV-exposed infants -~260 000 infants per annum in SA. [2] Hence, the RTHB has a pivotal role in improving communication between health workers and caregivers, empowering caregivers, enhancing continuity and co-ordination of care, as well as having the potential to assist with monitoring of national public health programmes, such as the PMTCT programme. [3] Although the World Health Organization (WHO) recommends that patientheld immunisation records be issued with a unique identifier, [1] SA's RTHBs are currently not issued with identifiers, despite being printed and distributed centrally.…”
Section: Researchmentioning
confidence: 99%